Assessment of Pain Perception of Elderly Patients with Different Levels of Dentophobia during Surgical Dental Appointment - Dorofeev, A. E. (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Elderly patients constitute a significant proportion of the population. All of them need skilled dental care. However, a significant proportion of patients is afraid of dental appointment. Premedication before a dental treatment is shown for all patients with a high level of anxiety. However, during studying the medical records of each patient, the significant number of comorbidities is identified which limit us in the use of medications for the prevention of stress and pain at the dental appointment. Aims: The aim of this study is to improve the quality of surgical dental care for elderly patients living in a gerontological center with different levels of dentophobia. This study evaluated the perception of pain of elderly patients with middle and high level of a dentophobia on surgical dental appointment. Materials and Methods: All patients, who participated in the study, live in geriatric center. All patients before surgery tooth extraction took the advice of a psychiatrist and neurologist. Patients with a high level of a dentophobia were held premedication over-the-counter medication and local anesthesia with a solution of 4% articaine with vasoconstrictor in a dilution of 1:200000. Premedication was not conducted for patients with middle level of dentophobia, and local anesthesia for them was done using 3% mepivacaine solution without vasoconstrictor. Evaluation of pain perception was carried out by the following methods: Electroodonto diagnosis, electromyography of facial muscles, sound eyes motor scale, and the visual analog scale. All the results obtained were processed in the program Statistical 6.0. Results: The results obtained using these methods have shown a reliable correlation between each other. Conclusions: The efficiency of premedication was proven as reducing the perception of pain of patients with high level of dentophobia.